ABOUT FOLK, ABOUT US AND ABOUT WORLD - Zemanová, Zuzana (Bohemica Olomucensia, 2013)
The review focuses on study Česká folková píseň v kontextu 60.-80. let 20. století written by Josef Prokeš and published in 2011, which deals with the creation of seven famous Czech folk singers connected to the period of 1960s-1980s (Karel Kryl, Jaroslav Hutka, Vladimír Merta, Vlastimil Třešňák, Jaromír Nohavica, Karel Plíhal, Slávek Janoušek), analyses their lyrics and describes their position in Czech folk music as well as in the life of society in general.